The nature of processing in working memory: temporal-contextual cues and characteristics - Loaiza-Kois, Vanessa Maria, author; McCabe, David P., advisor; Tracy, Brian L., committee member; Rhodes, Matthew G., committee member; Chavez, Ernest L., committee member (Colorado State University. Libraries, 2010)
The primary-secondary memory hypothesis proposes that processing in working memory requires maintaining activated representations in a capacity-limited primary memory while re-accessing representations from secondary memory that have been displaced when the limits of primary memory have been exceeded. An implication is that simple span list lengths that exceed primary memory involve the same temporal-contextual search of secondary memory that is utilized in all trials of a complex span task. A series of experiments tested whether a) temporal-contextual cues could successfully elicit items that were studied during operation span and supra-span trials of word span as opposed to sub-span word span trials, and b) whether temporal-contextual characteristics are more phenomenologically memorable for items studied in trials of operation span and supra-span trials of word span than for sub-span trials of word span. Temporal-contextual cues and characteristics, however, were more accessible for operation span items than for items from simple span at any list length. Implications are discussed in light of this recent theory of working memory capacity as well as models of temporal distinctiveness.
Keywords: Short-term memory